Event-shape engineering for inclusive spectra and elliptic flow in Pb-Pb collisions at √s NN = 2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Physical review, 2016)
We report on results obtained with the event-shape engineering technique applied to Pb-Pb collisions at √sNN=2.76 TeV. By selecting events in the same centrality interval, but with very different average flow, different initial-state conditions can be studied. We find the effect of the event-shape selection on the elliptic flow coefficient v2 to be almost independent of transverse momentum pT, which is as expected if this effect is attributable to fluctuations in the initial geometry of the system. Charged-hadron, -pion, -kaon, and -proton transverse momentum distributions are found to be harder in events with higher-than-average elliptic flow, indicating an interplay between radial and elliptic flow.